FROM ENGLISH AS A GENERAL SCHOOL SUBJECT ONTO ENGLISH AS A MEDIUM FOR LEARNING SPECIFIC SUBJECTS: THE NEED TO SHIFT IN THE TEACHING ORIENTATION - Kun Aniroh (TEFLIN, 2009)
Abstract: The teaching of ESP so far has been dominated by the belief that linguistic mastery of English is considered sufficient to deliver the contents of the subject matter concerned. This view seems to need a critical overview for verbal communication in general, let alone in ESP, requires both proficiency in the language and the contents. This implies that English teachers in ESP need to be equipped satisfactorily in English as well as the subject matter. An ESP teacher needs to possess a double competency. With this as a framework, the teaching of ESP accordingly will need to shift its focus from English in isolation to English as medium for subject matters exchanges.